ANALYSIS EFFECTIVENESS OF ADVERTISING ON WEB SERIES TO THE DECISION OF PURCHASING TROPICANA SLIM STEVIA (Study on Sore: Istri Dari Masa Depan Web Series) - Anisa Noor Fitriana; Sigit Tripambudi; Prayudi Prayudi (The Indonesian Journal of Communication Studies, 2018)
Web Series includes new media to advertise, the effectiveness seen in this research is after viewers watch the Web Series "Sore: Istri Dari Masa Depan" will take action to accept the existing products therein. This study aims to determine the audience response from the effectiveness of interactive advertising on the Web Series media to purchase decisions, and know how closely and how much influence the relationship that occurs therein. The theory used in this study is Interactive Advertising Model, which uses four indicators to see individuals using the media that is, functions, information processes, structures, and outcomes. Then use AIDA theory to see consumer response to purchasing decision by aligning attention, interest, consumer desire after seeing advertisement message that has been presented which will cause consumer action will receive the product. This type of research is survey research, spreading questionnaires on samples of the population that have been determined. Of the 100 questionnaires that have been distributed to obtain the results of Product Moment Correlation Analysis showed a correlation coefficient of 0.587 included in a positive positive relationship. The result of simple linear regression analysis shows that there is a significant influence between variables with percentage of 34.4%, while the remaining 65.6% (100% -34.4%) is explained by other variables outside the model in this study. The conclusion is that the web series media get a significant and positive influence but only 34.4%, because the younger respondents are more interested in how to communicate with interactive, interesting, educate healthy lifestyle, and make alternative entertainment, while to do the buying action after seeing Web Series has not arisen perfect because 65.6% of purchasing decisions of products from other variables.